PERLINDUNGAN HUKUM TERHADAP ANAK YANG LAHIR DARI PERKAWINAN DIBAWAH TANGAN. - Fatma Wati; Anis Mashdurohatun (UNISSULA Semarang, 2019)
In writing this journal background by the desire of the writer to know the legal protection of children born from marriage under the hands / sirri about the identity of children as it is known marriage under the hands / sirri not registered in the KUA in accordance with applicable law, even generally done secretly.The formulation of the problem / discussion in this journal is focused on (1) Position of Children Born of Marriage Below Hand / Marriage Sirri Regarding Child Identity. (2) Legal Protection Against Children Born of Marriage Below Hands according to the Constitutional Court's Decision (Mahkama Konstitusi). This journal can be useful for students and the public about the importance of knowing the legal rights and position of the child.Keywords: Child Protection, Marriage under the hand / sirri.